Decreased CD177pos neutrophils in myeloid neoplasms is associated with NPM1, RUNX1, TET2, and U2AF1 S34F mutations. (January 2022) - Alayed, Khaled; Meyerson, Howard J.
Highlights: Low percentage of CD177 pos neutrophils is associated with NPM1, RUNX1, TET2 and U2AF1 S34 F mutations. High percentage of CD177 pos neutrophils is associated with JAK2 mutations. TET2, RUNX1 and NPM1 mutations are associated with low percentage of CD177 pos neutrophils in AML but not in MDS or CCUS. Abstract: A decreased percentage of CD177 pos neutrophils is frequently present in MDS and AML and is a useful flow cytometry (FCM) marker for the identification of MDS. The underlying mechanism leading to the low percentage of CD177 pos neutrophils in MDS has not been explained. The aim of this study was to identify whether specific somatic mutations in myeloid neoplasms are associated with the low percentage of CD177 pos neutrophils. 507 myeloid neoplasms with one or more pathogenic molecular abnormality identified by NGS and in which CD177 expression was assessed were evaluated. Correlation with CD177 expression was determined for 39 variables (including genes mutated, diagnostic groups and gender) using a 40 % cutoff level for low CD177 expression. In multivariate analysis mutations involving NPM1 (OD 0.26), RUNX1 (OD 0.39), TET2 (OD 0.58), and U2AF1 S34F (OD 0.25) were associated with low percentage of CD177 pos neutrophils when all cases were evaluated. JAK2 (OD 2.5) alteration was associated with increased percentage of CD177 pos neutrophils. Differences were noted between diagnostic subgroups with no single mutation associated with decreased CD177 pos neutrophils in MDS and CCUS. The findings demonstrate an association between the percentage of CD177 pos neutrophils and somatically acquired mutations involving several genes.